CMC stabilized nano silver synthesis, characterization and its antibacterial and synergistic effect with broad spectrum antibiotics. (20th February 2017) - Prema, P.; Thangapandiyan, S.; Immanuel, G.
Highlights: Silver nanoparticles were synthesized by reduction of AgNO3 using aqueous CMC. These nanoparticles were characterized through UV spec., FTIR, XRD, SEM, EDS & AFM. Tested the antimicrobial activity of nanoparticles against human bacterial pathogens. The bacterial growth was highly inhibited by the nanoparticles. Synergistic effect (nanoparticles + antibiotics) was also tested against the bacteria. Abstract: In the present study silver nanoparticles were synthesized by reduction of AgNO3 using aqueous CMC solution, which acts as both reducing and capping agent. The formation of AgNO3 nanoparticles was observed visually by color change and these nanoparticles were characterized through UV–vis spectroscopy, FTIR, XRD, SEM, EDS and AFM. The FTIR peaks observed to be ranging from 3300 to 605 cm −1 . The AFM image clearly showed the surface morphology of well dispersed nanoparticles. SEM image illustrates the nanoparticles with spherical shape. The crystalline nature of the particles was assured by XRD analysis. The antimicrobial activity of nanoparticles was tested against human bacterial pathogens ( Bacillus cereus, Staphylococcus aureus, S. epidermidis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhimurium & Vibrio vulnificus ). The bacterial growth was highly inhibited by the nanoparticles. The synergistic effect of nanoparticles in combination with selected broad spectrum antibiotics against the tested bacteria determined strong growth inhibitory activity.